Use of Lisdexamfetamine or Amphetamine? Interpretation of Chiral Amphetamine Analyses. Issue 1 (20th November 2020) - Chermá, Maria D; Nilsson, Gunnel H; Johansson, Anna; Jönsson, Anna K; Ahlner, Johan
Abstract: Amphetamine is frequently detected in forensic toxicological cases. Differentiating between the two isomers of amphetamine (d-amphetamine and l-amphetamine) and determining their relative proportion are fundamental to correctly interpret the results of toxicological analyses. The aim of this study was to examine the profile of amphetamine as well as storage stability of the isomers in authentic samples from patients chronically treated with lisdexamfetamine (LDX), the most prescribed medical amphetamine product in Sweden. Blood and urine samples were collected from 18 patients. The samples were analyzed with an achiral (racemate) method for quantification of amphetamine and with a chiral method to determine the proportion of each isomer of amphetamine. The median daily dose of LDX was 40 mg (range, 20–70 mg). The median amphetamine concentration was 0.06 µg/g (range, 0.02–0.15 µg/g) in blood and 6 µg/mL (range, 1–22 µg/mL) in urine. Only d-amphetamine was found in the blood and urine samples from the included patients. Furthermore, no formation of l-amphetamine occurred during the storage for 3 months at 4°C, 9 months at −20°C and three freeze–thaw cycles. The results from this study may be helpful in the interpretation of whether the source of identified amphetamine in biological samples is from LDX drug intake or not.